Antecedents of continued use and extended use of enterprise systems. Issue 4 (3rd April 2019) - See, Boon Piow; Yap, Ching Seng; Ahmad, Rizal
ABSTRACT: This study examines the antecedents of continued use and extended use of Enterprise Systems (ES). Data were collected from 345 business executives through a self-administered questionnaire survey and are analysed using structural equation modelling (SEM). The results indicate that perceived usefulness, computer self-efficacy, and facilitating conditions are positively related to continued use and extended use of ES. However, neither continued use nor extended use is influenced by subjective norm. Additionally, users' continued use is significantly related to extended use, and it partially mediates the relationships between extended use and its antecedents. The findings of this study contribute to the existing literature on ES usage behaviour in the post-adoption phase and in the mandatory organisational context. For practice, these findings should give managers a better understanding of the antecedents of ES usage behaviours, which would, in turn, help organisations to develop strategies that encourage their employees to maximise the use of ES in performing their tasks.